The Effect of Bioethanol Blends with 92 Octane Gasoline on Engine Performance and Exhaust Emissions - yuniarto agus winoko; Achmad Walid; Mutrofin Rozaq; Akbar Anugrah (Asian Journal Science and Engineering, 2025)
This research focuses on the use of bioethanol mixed with 92-octane gasoline as an alternative fuel to improve engine performance and reduce emissions. The main problem addressed is the lack of optimization in the bioethanol and gasoline mixture ratio, which affects combustion efficiency and engine performance. The results show that mixing bioethanol with gasoline improves the brake mean effective pressure (BMEP) and decreases specific fuel consumption (SFC) at certain engine speeds, indicating enhanced combustion efficiency. However, the mixture ratio beyond a certain percentage (30% ethanol) leads to decreased performance, showing the limits of bioethanol use in fuel blends. The distinctive feature of this study is the comprehensive evaluation of different bioethanol proportions (13%, 15%, and 17%) and their effect on engine performance, providing more specific insights into the optimal fuel mixture for various engine conditions. The results are particularly useful for the automotive industry and policymakers looking to implement bioethanol as a sustainable alternative fuel